Institutional and technological innovations to transform informal milk markets in the eastern and central Africa region: preliminary lessons from action research - Lore, Tezira A.; Kurwijila, Lusato R.; Omore, Amos O. (International Livestock Research Institute, 2005)
This paper discusses preliminary lessons from action research to promote institutional and technological innovations aimed at transforming informal milk markets in East and Central African countries. Regulations affecting the dairy sectors in five selected countries were reviewed and factors limiting cross-border dairy trade documented. Dialogue among dairy experts and regulatory authorities was then undertaken to arrive at minimum standards of competence, build consensus on a regional guideline and curriculum to certify informal dairy traders and ensure cross-border recognition of certification by counterpart regulatory authorities and freer trade. The consultative process has fostered sharing of valuable experiences in improving the quality of informally marketed milk, and has helped influence changes in mindset among regulatory stakeholders, who are now more willing to support the development of informal milk markets. Generic work plans will be developed to facilitate the required actions.